INSTAGRAM: Bingkai Kasus Agama di Media Sosial - Aminuddin, Ahsani Taqwim (Jurnal The Messenger, 2017)
The religion issue is something sensitive in Indonesia. The defamation case that ensnared Basuki Tjahya Purnama by quoting Surah Al- Maidah verse 51 in his speech, so many people are distracted and angry because his words. Whereas technology increasingly sophisticated so that the dissemination of information so fast. Instagram as social media is currently booming among Indonesian teenagers could not ward from this problem conversation. Using framing model analysis method of Robert N. Entman researchers examined instagram contents that posted by official accounts belonging to three great Muslim organization in Indonesia, namely Muhammadiyah, Nahdlatul Ulama, and Front Pembela Islam, and found there is a dichotomy in the framing of this case in the official social media belonging to the Islamic organization i.e., (1) practice of trial by press; (2) whom to look out for; (3) who is wrong; (4) inviting to quiet vs indignant .